Dialektyka ruchu i pożądania w opowiadaniu W przedziale Stefana Grabińskiego - Kochanowski, Marek (Litteraria Copernicana, 2013)
Dialectics of motion and desire in A short story by Stefan Grabiński entitled W przedziale [In the compartment ] Abstract W przedziale [In the Compartment] is the third story in a collection by Stefan Grabiński entitled Demon ruchu [The Motion Demon]. The principal theme of this piece is the demonstration of the destructive force of brutal eroticism and crime that is a result of a fight for a woman played out in a compartment of a moving train. The actions of the main characters are motivated by the movement of the train, which in the text becomes independent of people and becomes the director of the actions of main protagonists. The article signals also a relationship between semantics of this story and an essay by Sigmund Freud, The Uncanny. The Freudian concept of the uncanny signifies the unknown, the inconvenient, the odd, something that comes to light particularly in various moments of “involuntary repetition”. In extreme cases, according to the narrator, human actions reveal a strong unidentified power that makes our capability of normative thinking insufficient to objectively assess a situation. The symbol of this eternal power can be a train, understood as an “icon of modernity”. The train motion turns protagonists into fragmentary characters broken down into basic units of stimuli, experiences and desires. Initiation into the sphere of what is hidden takes place in the story through motion, a demonic action of the machine that at the beginning of the twentieth century was not only seen as the symbol of advancement and technology, but was also associated with madness and death. Equally important in the analysed text is the compartment space that is a metaphorical place where an ideal machine is united with random emotions of its passengers.